(untitled) (Research, Society and Development, 2021)
The increase of surface roughness is a common measure for improving the slip resistance of floors. Nevertheless, the surface roughness of the floors can wear out during the use. Furthermore, rough surfaces can be susceptible to dirt accumulation. As a consequence, during the use, the original slip resistance and visual appearance of the floors can be deteriorated. In this scenario, the objective of this work was to evaluate the effects of pedestrian traffic on the surface profile, slip resistance and visual appearance of commercial ceramic floor tiles. The surface profile (contact profilometer), slip resistance (pendulum method) and visual appearance (visual analysis) of different commercial ceramic floors were evaluated before and after their exposure to heavy pedestrian traffic, and the results were compared. Significant reductions of the sharpness and height of profile peaks of the surfaces, due to mechanical wear, were observed. Consequently, for all the surfaces which initially presented satisfactory slip resistance for use in slipping risk areas, this property was reduced to unsafe levels. The degree of dirt accumulation, and the consequent visual appearance deterioration, varied according to the profile characteristics of the studied floors. The best cleaning performances were found for surfaces with more spaced irregularities and wider profile valleys.